2015
DOI: 10.1111/cen.12941
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends of body mass index in North Indian children with Type 1 diabetes do not support the Accelerator Hypothesis

Abstract: There was no association between BMI SDS and age at diagnosis in children with new onset T1D. Further studies are needed to test whether the accelerator hypothesis is relevant in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Dayal et al (22) recently reported that there was no association between BMI and age at diagnosis in North Indian children with new-onset type 1 diabetes. In addition, it has been reported that the incidence of type 1 diabetes continued to rise in 2001-2008 in Australian youth aged 10-18 years, while the incidence of type 2 diabetes remained steady (23).…”
Section: Prevalence Of Diabetic Nephropathymentioning
confidence: 98%
“…Dayal et al (22) recently reported that there was no association between BMI and age at diagnosis in North Indian children with new-onset type 1 diabetes. In addition, it has been reported that the incidence of type 1 diabetes continued to rise in 2001-2008 in Australian youth aged 10-18 years, while the incidence of type 2 diabetes remained steady (23).…”
Section: Prevalence Of Diabetic Nephropathymentioning
confidence: 98%
“…4 Our own study conducted in an ethnically different patient population and aimed at testing the AH in a developing country setup, demonstrated no association between BMI and age at diagnosis. 5 This was despite the fact that the prevalence of overweight and obesity in children has shown a significant average increase of 3% in our country during the time frame of our study. 6,7 Furthermore, the incidence of T1D at our hospital has also shown a significant increase over a similar time span.…”
mentioning
confidence: 59%
“…On the other hand, there are some concerns that high BMI might reflect heavier extent of insulin resistant and thus leading to the overload of β‐cell and then eventually accelerate the worsening of β‐cell function . Indeed, the “accelerator” or “overload” hypotheses had been proposed long ago, and researchers hold the thought that higher BMI might be the “accelerator” for T1D progression, but the reported results were conflicting …”
Section: Introductionmentioning
confidence: 99%